Electrochemical investigations of novel electrode materials. Progress report, 1 August 1978-31 July 1979. [Li/sub x/Na/sub 0/ /sub 18/ TiS/sub 2/ and Li/sub x/Na/sub 0/ /sub 18/ TaS/sub 2/ cathodes, Li anode] - Worrell, W. L. (Pennsylvania Univ., Philadelphia (USA), 1979)
Electrochemical investigations of the compositional variation of the chemical potential and chemical diffusivity of lithium in Li/sub x/TaS/sub 2/ and Li/sub x/TiS/sub 2/ were completed. The experimental results were used to increase understanding of the chemical bonding and transport mechanisms of lithium in the layered-structured intercalated disulfides. The major emphasis during the year was to expand earlier investigations of the co-intercalated disulfides: Li/sub x/Na/sub 0/ /sub 18/TaS/sub 2/ and Li/sub x/Na/sub 0/ /sub 18/TiS/sub 2/. Open-circuit voltage data clearly indicate that these co-intercalated compounds offer exciting possibilities as high-energy-density cathodes in lithium batteries. 2 figures.